A clinical registry of multisystemic presentation of hypovitaminosis D in hospital attendees in Kolkata - Roy Choudhury, Jayati; Bandyopadhyay, Debasmita; Mukherjee, Kheya; Bhattacharjee, Debojyoti (Asian Journal of Medical Sciences, 2022)
Background: Vitamin D (Vit D) is a steroid hormone essential for maintaining functional homeostasis in the body. Hypovitaminosis D has been a recognized worldwide problem affecting all age groups and sex. Its prevalence is very high in South Asia. Aims and Objectives: Therefore, this study was aimed to determine the spectrum of presentation of biochemical levels of hypovitaminosis D in Indian population in terms of age, sex, and multisystemic disorders. Materials and Methods: A cross-sectional study carried out on selective study population attending a tertiary care hospital from July 2019 to December 2020 with clinical presentations suspected to arise due to Vit D deficiency. Serum 25OH Vit D level was estimated by chemiluminescence method. Data were analyzed using GraphPad Prism 8. Results: Of the study population (n = 685), average serum 25(OH)D level in females and males was 24.13 ng/ml and 28.59 ng/ml, respectively. Significant difference in mean value of Vit D existed in males and females in the 21–40 years age group (p = 0.0048). Females in the Vit D deficient group (Vit D level<20) mostly presented with mastalgia (20.45%), low back pain (17.61%), and joint pain (11.36%). Common clinical presentation in males with Vit D levels less than 20 ng/ml was diabetes mellitus without CKD (18.34%), non-diabetic CKD (19.27%), and low back pain (16.51%). Conclusion: Low Vit D levels manifest itself as signs and symptoms involving various multisystemic disorders involving different age groups in both sexes. Early recognition and replacement can prevent the progress of complications which Vit D deficiency makes us prone to develop.